KAJIAN PSIKOLOGI TENTANG ISTIQAMAH PERSPEKTIF MAHASISWA - Husna, Hafizhah Al (Batanang : Jurnal Psikologi, 2024)
Abstract This study aims to analyze and prepare a conceptual framework that can be used as a research basis in Islamic Psychology. This research using a descriptive qualitative approach. The participants in this study were 57 students who were pursuing bachelor's and master's degrees, both on the island of Java and Sumatra. Research data was collected using the open-ended question method which contains one open question, namely "In your opinion, what is the meaning of istiqamah?ÔÇØ through the Google Forms platform. After the data is obtained, the responses will be included in the answer transcript and analyzed using thematic analysis (TA), by classifying the data into certain themes. To maintain the credibility of the data, the researcher used a data triangulation method of participant responses. The results of the study show that the meaning of istiqamah in the perspective of students is consistent, continuous, earnest and committed. These four meanings become important components for individuals in learning and become a determining factor for one's success in the academic field. Thus, these findings are able to become a contextual framework as a basis for the development of istiqamah psychology in the educational context. Keywords: academic, istiqamah, psychology.